Kegiatan Skrining Pemeriksaan Hemoglobin dan Hematokrit terhadap Penyakit Anemia pada Kelompok Lanjut Usia di Panti Werda Hana - Tan, Sukmawati Tansil; Firmansyah, Yohanes; Lumintang, Valentino Gilbert; Gunaidi, Farell Christian (Jurnal Kabar Masyarakat, 2024)
Anemia in the elderly is a common condition characterized by a decrease in red blood cells or hemoglobin levels, causing various health problems. Anemia is defined as a hemoglobin level below 13 g/dL in men and 12 g/dL in women. Various factors, such as inadequate nutritional intake, chronic inflammation, and kidney disease, often cause anemia in this population. Untreated anemia impacts quality of life, increases hospitalization rates, the risk of falls, and cognitive decline, and is independently associated with higher mortality from cardiovascular stress. This activity uses the PDCA (Plan-Do-Check-Action) method to screen and treat anemia in elderly participants Hana Nursing Home. We conducted complete blood tests on 61 respondents to evaluate their hematological profile. The blood test results revealed an average hematocrit of 36.15% for the participants, and anemia in 11 (18.03%) men and 19 (31.15%) women. Routine hemoglobin screening and effective management are essential for early detection and intervention, thereby improving the quality of life of the elderly. Keywords: Anemia, Elderly, Hemoglobin, Hematocrit